1995
DOI: 10.1128/jcm.33.10.2587-2591.1995
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nucleic acid-based test (PACE 2C) for simultaneous detection of Chlamydia trachomatis and Neisseria gonorrhoeae in endocervical specimens

Abstract: A nucleic acid-based test (Gen-Probe PACE 2C System) was evaluated for the ability to detect Chlamydia trachomatis and Neisseria gonorrhoeae from endocervical specimens in a single assay. Three swab samples, randomized for collection order, were obtained from each patient and tested by N. gonorrhoeae and C. trachomatis culture and by the PACE 2C probe assay. Fifty of 395 specimens were culture positive for N. gonorrhoeae (17 specimens), C. trachomatis (26 specimens), or both (7 specimens), of which PACE 2C tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…Our data confirm previous results suggesting that nucleic acid amplification-based assays for N. gonorrhoeae show a specificity equivalent to that of culture, but a sensitivity only slightly higher than that of culture for the diagnosis of infection with this organism in men (2,5,10). The sensitivity of LCR applied to FVU from men was only slightly less than that of the same assay applied to urethral swabs, suggesting that gonococcal infection can reliably be detected by LCR assay of this specimen that is obtained by noninvasive means.…”
Section: Discussionsupporting
confidence: 91%
“…Our data confirm previous results suggesting that nucleic acid amplification-based assays for N. gonorrhoeae show a specificity equivalent to that of culture, but a sensitivity only slightly higher than that of culture for the diagnosis of infection with this organism in men (2,5,10). The sensitivity of LCR applied to FVU from men was only slightly less than that of the same assay applied to urethral swabs, suggesting that gonococcal infection can reliably be detected by LCR assay of this specimen that is obtained by noninvasive means.…”
Section: Discussionsupporting
confidence: 91%
“…Nucleic acid amplification tests have generally been more sensitive than traditional tests for the detection of C. trachomatis (7,10,14,16,19,20,22,23), but they have not been extensively evaluated for N. gonorrhoeae. Although multiplex PCR (M-PCR) has been applied to the detection of multiple viruses in clinical specimens (1,21,27,29), this approach to diagnosis has only recently been applied for the detection of bacterial STDs (13,24). We report here the development of an M-PCR for the simultaneous detection of C. trachomatis and N. gonorrhoeae in genitourinary specimens and show that M-PCR is more sensitive than traditional tests for these STDs.…”
mentioning
confidence: 97%
“…The enzyme immunoassay methods have reported sensitivities ranging from 60.8% (12) to 92.4% (5) when tested on female endocervical specimens and 62.5% (11) when tested on female urine specimens. The DNA probe assay has a reported sensitivity ranging from 96.3% (7) to 100% (10) and a specificity of greater than 99% (6,7,10,13). In several studies comparing culture to DNA probe assays, reported culture sensitivities have ranged from 88.9% (7) to 90.6% (10).…”
mentioning
confidence: 99%
“…The DNA probe assay has a reported sensitivity ranging from 96.3% (7) to 100% (10) and a specificity of greater than 99% (6,7,10,13). In several studies comparing culture to DNA probe assays, reported culture sensitivities have ranged from 88.9% (7) to 90.6% (10). This suggests that molecular methods may be an improvement over traditional culture.…”
mentioning
confidence: 99%